Social capital as a resource influencing social and economic processes - Kis, Krisztián (Acta Agraria Debreceniensis, 2006)
The concept of social capital became well-known in the 1980s and as a non-material resource existing in the society and today it is one of the most popular fields of the sociological and economic research. There are many definitions of social capital, but there is a common point that they all have: a network-related interpretation. The networks are made up of discrete elements, which have some kind of relation between them. Accordingly, social capital is manifested in the totality of the relations between elements (actors of the economy and society) forming the network not in the elements themselves (e.g. human capital). This is a resource which influences the social and economic processes of a community – even if it is a community of a micro region or a nation. Consequently, social capital has a significant impact on the development and improvement of an area or a territorial unit. In this paper, I try to summarise the information concerning social capital and to sketch the relation between rural development and social capital as one of the immanent resources of a territorial unit.